Analysis of Changes in Traumatic Symptoms and Daily Life Activity of Children Affected by the 2011 Japan Earthquake and Tsunami over Time - Usami, Masahide (Public Library of Science, 2014)
BACKGROUND: On March 11, 2011, Japan was struck by a massive earthquake and tsunami. The tsunami caused tremendous damage and traumatized a number of people, including children. This study aimed to compare traumatic symptoms and daily life activity among children 20 months after the 2011 Great East Japan Earthquake and Tsunami with those observed after 8 months. METHODS: The study comprised two groups. The first comprised 12,524 kindergarten, elementary school, and junior high school children in Ishinomaki City, Miyagi Prefecture, Japan, who were evaluated 8 months after the disaster. The second comprised 10,597 children from the same place who were evaluated 20 months after the disaster. The Post Traumatic Stress Symptoms for Children 15 items (PTSSC-15), a self-completion questionnaire on traumatic symptoms, and a questionnaire on children's daily life were distributed to the children. An effective response was obtained from 11,639 (92.9%, 8 months after) and 10,597 (86.9%, 20 months after) children. RESULTS: The PTSSC-15 score was significantly higher in junior high school girls than in boys. The PTSSC-15 score was significantly higher in 4th–6th grade girls than in boys after 8 months. Elementary and junior high school children evaluated after 20 months had a significantly lower PTSSC-15 score than those evaluated after 8 months. The number of children having breakfast was significantly higher after 8 months than that after 20 months. In both the groups, children of all grades who had breakfast had a significantly lower PTSSC-15 score than those who did not have breakfast. CONCLUSIONS: We conclude that traumatic symptoms and daily life activity of children who survived the earthquake and tsunami improved over time.